Contemporary global trends in instructional design: the role of lesson study in designing meaningful lessons among teachers - Khalid, Madihah (2017)
As teachers/lecturers, we have the obligation to teach properly. Meaningful learning happens when students understand or are able to make sense of the lesson taught and meaningful lesson is associated with good instructional design, The change in syllabus to meet the demands of the 21st century learning has resulted in a lot of pressure on teachers and instructors to keep up with the most up-to-date trends. The call to embed a balanced set of knowledge and skills such as thinking, innovation, problem-solving and leadership skills requires careful planning of the lesson so that the reform effort is successful. While teachers are faced with this problems, there has been many initiatives to help them by encouraging them to work together in collaboration such as in instructional coaching and professional learning community (PLC). One of the related trends that is being practiced nationally and globally is lesson study. This paper will look at how lesson study has helped instructors in lesson planning and hence designing meaningful lessons. The paper will touch on some history of lesson study and how it has helped teachers in improving their content and pedagogical content knowledge nationally and globally, which resulted in improved instructional design.